2021
DOI: 10.1088/1742-6596/1808/1/012051
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Mathematical External Connection Ability Based on Personality Types of Sensing Intuition

Abstract: Mathematical external connection ability is the ability to relate topics in mathematics to the other learning subject and daily problems. Sensing and intuition personality is a characteristic of students receive and process information. For this reason, personality types can influence mathematics learning and mathematical external connection ability. The main purpose of this research is analysis of students’ external connection skill that has sensing or intuition personality. This study method used was descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The results of research by [16] revealed that the application of community-based brain-based learning has a significant effect on students' mathematical connection abilities. In line with the findings of [8] that the Instagram-assisted brain-based learning approach is effective in solving math problems. Thus the brainbased learning approach can be an alternative means to significantly improve students' mastery of mathematical concepts.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results of research by [16] revealed that the application of community-based brain-based learning has a significant effect on students' mathematical connection abilities. In line with the findings of [8] that the Instagram-assisted brain-based learning approach is effective in solving math problems. Thus the brainbased learning approach can be an alternative means to significantly improve students' mastery of mathematical concepts.…”
Section: Introductionsupporting
confidence: 84%
“…The readiness of teachers and students in adopting technological literacy requires a long time. According to the research results of [7] Reveals that students almost experience difficulties in implementing mathematics learning strategies at home with high stress and anxiety levels The results of research by [8] reveal that students' mathematical connection skills are still low. This can be seen from the indicators that show that students are less capable in modelling contextual questions correctly, students are not able to apply concepts and procedures, students have difficulty developing mathematical ideas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation